2018
DOI: 10.5147/ajb.v0i0.172
|View full text |Cite
|
Sign up to set email alerts
|

Verticillium dahliae-eggplant as the pathosystem model to reveal biocontrol potential of three Trichoderma spp in green house conditions

Abstract: In this study three Trichoderma species isolated from Moroccan soil (natural and agricultural habitats) were investigated for their biocontrol potential against virulent Verticillium dahliae on eggplant in green house conditions based on dipping root approach. Evaluation of biocontrol efficacy of Trichoderma spp. demonstrated effective potential of Trichoderma on reducing Verticilium disease on eggplant cultivars. Disease assessment was established by measuring disease incidence in root units (DI-RU) and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…When the effects of the application of biological control agents together with the pathogen on plant growth parameters were examined, it was found that the combined treatments of Trichoderma and PGPR caused an increase in stem diameter, stem length, stem fresh and dry weights, root length, root fresh and dry weights of eggplants, compared to the treatments performed separately. It was previously reported that Trichoderma species (Mokhtari et al 2018) and PGPR isolates (Guenoun et al 2018) increased plant growth parameters in eggplant infected with V. dahliae.There are also reports on increased plant growth parameters as a result of the separate and combined treatments of Trichoderma and PGPR isolates on plants infected with different pathogens (Thilagavathi et al 2007;Morsy et al 2009;Chowdappa et al 2013;Erper et al 2013;Kumar et al 2015). As a result of this study, it was found that Trichoderma and PGPR applications increased the activities of defence-related enzymes peroxidase, polyphenol oxidase, phenylalanine ammonium lyase and β-1,3 glucanase on eggplant seedlings inoculated with V. dahliae.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…When the effects of the application of biological control agents together with the pathogen on plant growth parameters were examined, it was found that the combined treatments of Trichoderma and PGPR caused an increase in stem diameter, stem length, stem fresh and dry weights, root length, root fresh and dry weights of eggplants, compared to the treatments performed separately. It was previously reported that Trichoderma species (Mokhtari et al 2018) and PGPR isolates (Guenoun et al 2018) increased plant growth parameters in eggplant infected with V. dahliae.There are also reports on increased plant growth parameters as a result of the separate and combined treatments of Trichoderma and PGPR isolates on plants infected with different pathogens (Thilagavathi et al 2007;Morsy et al 2009;Chowdappa et al 2013;Erper et al 2013;Kumar et al 2015). As a result of this study, it was found that Trichoderma and PGPR applications increased the activities of defence-related enzymes peroxidase, polyphenol oxidase, phenylalanine ammonium lyase and β-1,3 glucanase on eggplant seedlings inoculated with V. dahliae.…”
Section: Discussionmentioning
confidence: 93%
“…The lowest disease rate was obtained with the separate and combined treatments of T. atroviride with PGPR. In the previous studies on the effects of biological control agents against V. dahliae, it was also observed that single Trichoderma and PGPR treatments decreased disease severity rates, but the symptoms did not disappear completely and the application time of biological control agents also affected the disease severity (Amini 2017;Guenoun et al 2018;Mokhtari et al 2018;Zhang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the potential of Trichoderma to reduce Verticillium wilt in different annual crops such as strawberry (Mirmajlessi et al, 2016), cotton (Hanson, 2000;Naraghi et al, 2012), eggplant (Solanum melongena L.) (Mokhtari et al, 2018), andtomato (Jabnoun-Khiareddine et al, 2009) as well as in woody hosts such as olive, pistachio, and avocado (Supplementary Table 1). However, only one study has been conducted on the use of Trichoderma for VW control in cacao (Leon-Ttacca et al, 2019a;Leon-Ttacca et al, 2019b).…”
Section: Biological Control Of Verticillium Wilt Of Cacaomentioning
confidence: 99%